Assessing the effect of regular swimming exercise on the micro- and macrovascular physiology of older adults (ACELA II study) - Klonizakis, M.; Mitropoulos, A. (Frontiers in Physiology, 2023)
Introduction: Cardiovascular disease (CVD) remains the main cause of death in the Western world. Our recent findings demonstrate potential CVD risk reduction in older adults who undertake regular swimming exercise. Nevertheless, it remains unknown whether an exercise intervention based on swimming is feasible and effective prior to a wider implementation of a CVD risk prevention strategy. Methods: This was a pragmatic, two-group, randomised controlled trial. A total of 40 older adults were randomly split into two groups (n = 20 per group). The swimming exercise group consisted of participants who engaged in swimming exercise (2–3 days/week, for 8 weeks). The control group did not perform any exercise. Flow-mediated dilation (%FMD) was the primary outcome. Secondary outcomes included raw cutaneous vascular conductance. Feasibility outcomes (e.g., recruitment, adherence, and attrition rates) were also assessed. Results: Statistically significant macrovascular (%FMD; swimming group: 9.8% ± 4.2%, p <0.001; control group: 4.6% ± 2.5%) and microvascular function (raw cutaneous vascular conductance; swimming group: 4.1 ± 0.9, p <0.01; control group: 3.2 ± 1.1) improvements were observed in the swimming group compared to the control group. Compliance to twice and thrice weekly in an 8-week swimming exercise was 92.6% and 88.4%, respectively, with no dropouts. Conclusion: Our 8-week, community-based, pragmatic swimming exercise intervention is a feasible and effective exercise programme that could be implemented in older adults for the prevention of age-related CVD. These findings suggest that swimming exercise could significantly reduce CVD risk in older adults, and a large research clinical trial is warranted to establish these findings.